The Effect of Cost Control on The Survival of Manufacturing Sectors in Nigeria: Panel Data Analysis. - Isiaka, Najeem Ayodeji; Ayuba A Jimoh; Orebiyi, Mary Ayomide; Adenekan, Sheriff Abayomi (Asean International Journal of Business, 2022)
The persistent decline in the survival of manufacturing sector in Nigeria, especially during recession has spurred research interest amongst professionals, researchers and scholars. Despite the huge attention given to the development of manufacturing sectors, a good number of companies cannot withstand the poor economic wave. This necessities the study to examine the effect of cost control strategies on the survival of manufacturing sector in Nigeria, using panel data gathered from annual reports of five selected firms for the period five (5) years between 2015 and 2019. Data on finance cost, salaries, and wages, and sales cost were taken as independent variables to measure the level at which manufacturing companies have been able to manage their costs while return on asset (Income/Total Asset) was taken as dependent variable proxied the performance of manufacturing companies. The study revealed that finance cost and cost of goods sold were insignificant cost to influence the performance of manufacturing sector, however, salaries and wages pose a significant impact on financial performance of manufacturing sector in Nigeria. It is therefore recommends that salaries and borrowing costs should be strategically controlled to help companies survive during recession without resorting to downsizing. Also, the company budget should not be fixed, but should be revised to reflect any sudden changes in the economy.